If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + -3 + -1 = 3c + 2 Reorder the terms: -3 + -1 + 6c = 3c + 2 Combine like terms: -3 + -1 = -4 -4 + 6c = 3c + 2 Reorder the terms: -4 + 6c = 2 + 3c Solving -4 + 6c = 2 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. -4 + 6c + -3c = 2 + 3c + -3c Combine like terms: 6c + -3c = 3c -4 + 3c = 2 + 3c + -3c Combine like terms: 3c + -3c = 0 -4 + 3c = 2 + 0 -4 + 3c = 2 Add '4' to each side of the equation. -4 + 4 + 3c = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 3c = 2 + 4 3c = 2 + 4 Combine like terms: 2 + 4 = 6 3c = 6 Divide each side by '3'. c = 2 Simplifying c = 2
| 10-7x=170-42x | | lg(4x+5)=lg(5x+2) | | -10+2a=4a+4-2 | | x=5+-5y | | -10-6x=23-3x | | 6(x+4)=3(2x+2) | | -4s-7=13 | | (1/10)x=30 | | 3t-6=4t+20 | | 3/4=x/100 | | y^2-5y=24 | | 5x-29=-2x+20 | | x-(12-25)=38 | | 2a^2+6=206 | | 8(cd)=(8c)d | | 2a*b+(2a*2b/2) | | -24+x=12+5x | | 144x^2-16= | | 3x-3-9=0 | | -3+y=-8 | | -26+5x=-6x+40 | | 64n^2-10=-6 | | -11-(-34)=x/2 | | 9n/n-42n+49 | | 6x-1=10x-49 | | -4-4x=1-2x-3x | | 65+5y-28=14y-12-2y | | -19m+12=-14-8 | | x/-2-3=18 | | 2x-51=26-5x | | 8-6b^2=-268 | | 5d-(2a+8)=0 |